2017
DOI: 10.1097/mej.0000000000000320
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of screening and brief intervention for hazardous alcohol use integrated into clinical practice in an inner-city Emergency Department

Abstract: Our study shows that in a large inner-city ED, SBIRT can be implemented in daily care. Screening uncovered large numbers of patients with hazardous alcohol use and identified several risk factors. Moreover, screening and intervention appeared to be effective in reducing alcohol intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…It includes emergency department or urgent care center, prescribing a medicine that interacts with alcohol, and so on [ 8 ]. Many studies have shown that brief intervention about alcohol drinking in emergency department is effective [ 9 12 ]. Emergency department is an important clinical place for screening at-risk drinking and conducting brief intervention.…”
Section: Introductionmentioning
confidence: 99%
“…It includes emergency department or urgent care center, prescribing a medicine that interacts with alcohol, and so on [ 8 ]. Many studies have shown that brief intervention about alcohol drinking in emergency department is effective [ 9 12 ]. Emergency department is an important clinical place for screening at-risk drinking and conducting brief intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Studies performing SBIRT according to this approach reported a lower number of unscreened patients 20 21. Adopting narrower screening criteria may decrease costs and increase specificity, especially when the occurrence of hazardous alcohol use in the total ED patient population is low 6–8 22…”
Section: Discussionmentioning
confidence: 99%
“…The SIREN study was performed from November 2012 to November 2013 in the ED of Haaglanden Medical Centre Westeinde (HMC Westeinde) 6. The HMC Westeinde is an inner city general hospital and level I trauma centre in the Netherlands, with 50 000 ED visits annually.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations